A Comparison of the Batterer Intervention and Prevention Program With Alternative Court Dispositions on 12-Month Recidivism. (August 2016) - Boots, Denise Paquette; Wareham, Jennifer; Bartula, Aaron; Canas, Roberto
Studies of batterer intervention and prevention programs (BIPPs) offer mixed results regarding their effect on recidivism. The purpose of this study was to examine the effectiveness of BIPP for cases assigned to a misdemeanor family court. This study focused on determining whether BIPP cases, compared with alternative sanctions, had significantly lower recidivism rates 12 months after program involvement. Findings indicated that BIPP was more effective than jail or regular dismissal in reducing the likelihood of future arrests, but not plea deferred adjudication and conditional dismissal. Results argue toward the efficacy of some form of treatment versus simply receiving jail time.